Moving to paradise for the children’s sake - Korpela, Mari (Migration Letters, 2018)
Increasing numbers of “Western” families spend several months a year in Goa, India, and the rest of the time in the parents’ passport countries or elsewhere. These “lifestyle migrants” are motivated by a search for “a better quality of life”, and the parents often claim that an important reason for their lifestyle choice is that it is better for the children to be in Goa, where they have enriching experiences and enjoy playing freely outdoors, in a natural environment. This article discusses parents’ and children’s views of this lifestyle. It argues that although the lifestyle sometimes causes moral panic among outsider adults who see regular transnational mobility as a sign of instability, a closer look reveals that there are various aspects of stability in the children’s lives. Paying careful attention to the parents’ and children’s own accounts, and the empirical realities of their lives, enables us to reach beyond normative judgements.